Advances in treatment strategies for ischemia reperfusion injury. (22nd January 2016) - Pantazi, Eirini; Bejaoui, Mohamed; Folch-Puy, Emma; Adam, René; Roselló-Catafau, Joan
ABSTRACT: Introduction : Ischemia-reperfusion injury (IRI) involves a complex sequence of events and limits the outcome of various surgical interventions. Clinical trials, based on the data of experimental models, aim to prove whether a pharmacological or technical approach could be suitable to provide a beneficial effect in humans. Due to the complexity of IRI, few pharmacological treatments have been investigated in clinical Phase III. Areas covered : In this review we report clinical trials that test specific drugs in clinical trials of organ transplantation. These studies form part of Phase II trials and examine the administration of caspase inhibitors, P-selectin antagonist or an antioxidant component in order to attenuate cold IRI during transplantation. Moreover, we provide a brief description of drugs tested on trials of different clinical situations associated to IRI, such as the coronary artery bypass graft surgery and percutaneous coronary intervention. Expert opinion : Future clinical trials could be centered on the application of techniques suitable for organs with increased vulnerability toward IRI. Furthermore, the standardization of reliable biomarkers and a careful estimation of the impact of high risk factors may be the key in order to achieve a more critical evaluation of the obtained results.